Hybrid materials based on aluminum tungstophosphate or tungstosilicate as catalysts in anisole acylation - Fuchs, Vanesa Maria (2008)
New hybrid materials were prepared by the immobilization of aluminum tungstophosphate or tungstosilicate in a polymeric blend formed by polyvinyl alcohol and polyethylene glycol by the freeze-thawing method. The salts retained the Keggin structure of the heteropolyanions during their synthesis and immobilization. Materials with spherical shape and a mean size of 2 mm were obtained, with an almost constant distribution of the salts along the sphere width. Besides, the immobilized salts presented very strong acid sites. The synthesized catalysts showed an excellent yield in anisole acylation with a catalytic activity higher than that of the catalyst obtained from AlCl3 immobilized in the same polymeric matrix, related to a higher effectiveness in acylium ion formation of Keggin heteropolyanions with respect to chloride, due to their soft base nature. © 2007 Elsevier B.V. All rights reserved.